PERBANDINGAN METODE DYNAMIC CELL SPREADING (DCS) DAN SPREAD SPECTRUM PADA STEGANOGRAFI BERBASIS APLIKASI WEB - Wamiliana Wamiliana; Astria Hijriani; pita utari ningtyas (Universitas Lampung, 2017)
The security is the most important thing in sending a secret message and there are many ways to send a message safely, one of those is steganography. In this research we will compare Dynamic Cell Spreading (DCS) and Spread Spectrum method based on web application using image as the media and hide the secret message. The file format used are (.jpg) as input cover,(.png) as output stegoimage, and (.txt) as data that can be inserted. Doing some test to manipulate brightness, contrast, and cropping the results show that Spread Spectrum method better than Dynamic Cell Spreading method. The Spread Spectrum method mostly returns the message in the brightness and contrast manipulation. Cropping stegoimage on the right area or bottom image has less risk of losing data depend on the cropping scale and image resolution.